(c+3)-2c-(1-3c)=32

Simple and best practice solution for (c+3)-2c-(1-3c)=32 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (c+3)-2c-(1-3c)=32 equation:


Simplifying
(c + 3) + -2c + -1(1 + -3c) = 32

Reorder the terms:
(3 + c) + -2c + -1(1 + -3c) = 32

Remove parenthesis around (3 + c)
3 + c + -2c + -1(1 + -3c) = 32
3 + c + -2c + (1 * -1 + -3c * -1) = 32
3 + c + -2c + (-1 + 3c) = 32

Reorder the terms:
3 + -1 + c + -2c + 3c = 32

Combine like terms: 3 + -1 = 2
2 + c + -2c + 3c = 32

Combine like terms: c + -2c = -1c
2 + -1c + 3c = 32

Combine like terms: -1c + 3c = 2c
2 + 2c = 32

Solving
2 + 2c = 32

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 2c = 32 + -2

Combine like terms: 2 + -2 = 0
0 + 2c = 32 + -2
2c = 32 + -2

Combine like terms: 32 + -2 = 30
2c = 30

Divide each side by '2'.
c = 15

Simplifying
c = 15

See similar equations:

| -2u+(-3.5)=4.5 | | 0.625(x-0.33333)=0.416667 | | t^5-256t=9 | | (8-2z)/52 | | -x+3=-34 | | 35/42 | | 28-3x+3x+30-3x=40 | | X+64-42=104 | | 6.55=v/2-(-5.45) | | 15-y=273 | | 4-2x=2(x+4) | | 10x-10+10X=180 | | 4x-10+10X=180 | | y+2=-3(x+6) | | F=-9c+80 | | 4x-10+11X=180 | | 6-v=157 | | -7/8x2 | | (105x+9.5)=(14.75) | | 4x-15+11X=180 | | 12+6p+3q-5p+7p-2= | | 8x-16+3x-8=4x | | 5y+4=4w+5 | | -6+(-2x)=10*2-x | | 1.54/1.1 | | -0.571429(x-0.25)=0.428571 | | 32=3y-3+2y | | 3x+5+6x=77 | | 6(-1+5x)=294 | | 5p+3q=-25 | | 7x-4=3x+14 | | 9x-(3x+6)=7x-24 |

Equations solver categories